Infants' Sleep: Israeli Parents' Knowledge, Attitudes and Practices - Anat Shatz; Leon Joseph; Liat Korn (MDPI AG, 2021)
The purpose of the study was to assess Israeli parents' knowledge of and attitudes towards practices promoting infants' safe sleep and their compliance with such practices. Researchers visited the homes of 335 parents in 59 different residential locations in Israel and collected their responses to structured questionnaires. SPSS 25 statistical package for data analysis was used. Attitude scales were created after the reliability tests and scaled means of parental attitudes were compared between independent groups differentiated by gender, ethnicity, and parental experience. A logistic regression was run to predict the outcome variable of babies' sleep positions. The total knowledge score was significantly higher for women (56.3%) than for men (28.6%; p < 0.001). Arabs were more committed to following recommendations (29.3%) than Jews (26.9%; p < 0.001). Consistent with safe sleep recommendations, 92% of the sampled parents reported avoiding bedsharing and 89% reported using a firm mattress and fitted sheets. The risk of not placing a baby to sleep in a supine position was higher among older parents (adjusted odds ratio-AOR = 0.36, 95%CI 0.16-0.82), smoking fathers (AOR = 2.66, 95%CI 1.12-6.33), parents who did not trust recommendations (AOR = 4.03, 95%CI 1.84-8.84), parents not committed to following recommendations (AOR = 2.83, 95%CI 1.21-6.60), and parents whose baby slept in their room (AOR = 0.38, 95%CI 0.17-0.88). Knowledge of safe sleep recommendations was not associated with actual parental practices. Trust of and commitment to recommendations were positively correlated with safe sleep position practices. It is essential to develop ethnic-/gender-focused intervention programs.